Deteksi Dini Perkembangan Sosial Kemandirian Anak Usia 6 Tahun melalui Observasi Kegiatan Bermain di TK Al Jamaiyah: Penelitian - Khadijah; Indri Nursajidah; Tria Andriani; Putri Mawardah Lubis; Wardah Hayirani Lubis (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Social development and independence are important aspects in the growth of 6-year-old children, who are in the transition period to primary education. This study aims to detect early social development and independence of children through observation of play activities at Al Jamaiyah Kindergarten. The research approach used a qualitative descriptive method with purposive sampling techniques, direct observation, checklists, field notes, and anecdotal notes. The observation results show variations in development: children in the Very Well Developing category, such as Baim, Devan, and Satria, have mature social skills and stable independence; those in the Good to Good Developing category, such as Aznah, Halisa, and Mutia, show positive development but still need to strengthen consistency and emotional management; while children in the Needs Stimulation and Needs Special Attention category, namely Kaira and Zea, face challenges in self-regulation, social interaction, and decision-making. Play observations provide authentic images, enabling teachers and parents to provide appropriate stimulation and interventions so that children's social development and independence develop optimally.